2020
DOI: 10.1785/0120190062
|View full text |Cite
|
Sign up to set email alerts
|

Large Isotropic Component in the Source Mechanism of the 2013 Democratic People’s Republic of Korea Nuclear Test Revealed via a Hierarchical Bayesian Inversion

Abstract: The 12 February 2013 nuclear test conducted by the Democratic People’s Republic of Korea stands out among other nuclear tests because it produced unusually large transversal motions. Previous studies found various percentages of isotropic components of the seismic moment tensor (MT), which opens up an important question about the reliability of the methods and assumptions we routinely use to recover the seismic MT in the point source approximation. Of particular interest is the data noise model that can be uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Such a combination of subevents could be associated with the collapse of magma chamber followed by a ring-type rupture along the walls of the caldera (Fichtner & Tkalčić, 2010;Tkalčić et al, 2009). Similar scenario could be associated with nuclear explosions, where a volumetric explosion may trigger slip on nearby faults (e.g., Mustać et al, 2020). Although the estimation of CLVD and its interpretation are quite challenging, it has been associated with interesting phenomena, such as volcanic activities, fluid motions, tensile cracks, and fault complexity (see recent examples in Fontaine et al, 2019;Liu & Zahradník, 2020;White et al, 2019).…”
Section: A Caldera Collapsementioning
confidence: 95%
See 2 more Smart Citations
“…Such a combination of subevents could be associated with the collapse of magma chamber followed by a ring-type rupture along the walls of the caldera (Fichtner & Tkalčić, 2010;Tkalčić et al, 2009). Similar scenario could be associated with nuclear explosions, where a volumetric explosion may trigger slip on nearby faults (e.g., Mustać et al, 2020). Although the estimation of CLVD and its interpretation are quite challenging, it has been associated with interesting phenomena, such as volcanic activities, fluid motions, tensile cracks, and fault complexity (see recent examples in Fontaine et al, 2019;Liu & Zahradník, 2020;White et al, 2019).…”
Section: A Caldera Collapsementioning
confidence: 95%
“…A common practice in regional CMT inversion is to derive a 1‐D local Earth model from existing information, and sometimes multiple 1‐D models for each source‐receiver paths are preferred (e.g., Mustać et al, 2020). To test a similar approach, we performed CMT inversion using a 1‐D velocity model derived from the 3‐D AusREM model beneath the source region of the earthquake.…”
Section: May 2016 Petermann Ranges Earthquakementioning
confidence: 99%
See 1 more Smart Citation
“…Since a couple of years, the progress in computational and storage resources allowed to investigate the usage of 3-dimensional (3D) structural models for various studies, including regional waveform inversion for moment tensors (e. g. Hingee et al, 2011;Zhou et al, 2016;Hejrani et al, 2017). Several authors have shown that the usage of 3D structural models can be strongly beneficial for the reliability of the inversion result, that means the seismic moment tensor (e. g. Fichtner and Tkalčić, 2010;Kim et al, 2011;Covellone and Savage, 2012;Kühn and Vavryčuk, 2013;Hejrani and Tkalčić, 2020). It allows to extend the waveform inversion to higher frequency ranges, but still below the corner frequency, because the chances to decipher the more complex waveforms due to more detailed structure increase.…”
Section: Influence Of Frequency Range and Structural Modelmentioning
confidence: 99%
“…The determination on a regional (or even local) scale is more complicated. The stability of the waveform inversion result is affected by less well-known structural models (e. g. Šilený, 2004;Vasyura-Bathke et al, 2021), influence of theoretical and measurement noise (e. g. Sipkin, 1986;Duputel et al, 2012;Mustać et al, 2020), unfavourable event-receiver geometries (e. g. Dreger and Helmberger, 1993;Delouis and Legrand, 1999), ignored source complexities (e. g. Adamova andŠilený, 2010), and limitations of methodological approaches (e. g. Fan and Wallace, 1991;Frohlich, 1994;Julian et al, 1998;Cesca and Heimann, 2018).…”
Section: Introductionmentioning
confidence: 99%